1991
DOI: 10.1111/j.1464-410x.1991.tb15291.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour Duplex Sonography in the Assessment of Impotence

Abstract: We present our experience with colour duplex sonography (Acuson 128) in the assessment of 83 impotent men. Cavernosal artery measurements were taken before and after the intracorporeal injection of papaverine. The peak velocities following papaverine injection correlated well with the degree of clinical response. Percentage diameter change corresponded with some groups of clinical erection grade, although it was not as good a discriminator as peak velocity. Twelve patients with 24 cavernosal arteries were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…As in previous studies, we found the percentage change in CAD to be the least reliable parameter of arterial disease, because of the difficulty in measuring the small arterial CA diameters accurately and reproducibly. 24 A caveat of this study is the lack of control preoperative Doppler measurements, measurements in a cohort of sildenafil-responsive men, and men with normal erectile function after RRP. It is possible that, although the prevalence of arterial disease in this population was low, it might have been even lower pre-operatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous studies, we found the percentage change in CAD to be the least reliable parameter of arterial disease, because of the difficulty in measuring the small arterial CA diameters accurately and reproducibly. 24 A caveat of this study is the lack of control preoperative Doppler measurements, measurements in a cohort of sildenafil-responsive men, and men with normal erectile function after RRP. It is possible that, although the prevalence of arterial disease in this population was low, it might have been even lower pre-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of penile Doppler in the determination of arterial disease has been established. 24,25 Arterial disease appears to be a major factor in non-RRP men failing sildenafil. 18 We therefore questioned whether this might be the case after RRP.…”
Section: Discussionmentioning
confidence: 99%
“…Nine patients also represented various other medical diseases, including diabetes in two, hypertension in three, myocardial infarction in one, parkinsonism in one, CVA in one and neurosis in one. The methods employed in the present study have been described in more detail in our previous work [17]. All patients were extensively informed about the study and the possible side effects and gave written informed consent.…”
Section: Removal Of Endotheliummentioning
confidence: 99%
“…Others have found that arteriographic examinations of the iliopudendal vascular system is improved after intracavernosal injection of a papaverine-phentoalamine drug combination. 12 Extremely anxious patients may not respond appropriately to a vasodilator, and additional sedation may be necessary to relieve some of the anxiety.…”
Section: Pudendal Arteriographymentioning
confidence: 99%